Pembentukan Identitas Pada Fandom POLCA - Fauziyyah, Khoirunnisa; Silvia, Putri Jasmin; Pandora, Farisya Tsani; Anzani, Kinanggih; Aryanti, Marsela Pretisa; Abidin, Zainal (Jurnal Ilmiah Wahana Pendidikan, 2025)
This research delves into the identity and community life within the Polca fandom through an ethnographic approach. Data were collected through online surveys, interviews with Polca community members, and participatory observation in community activities. The results of the study indicate that members of the Polca community have a strong identity based on their love for Tay and New, as well as shared values and norms. Reciprocal support, creativity, and a sense of belonging are also key elements in creating meaning within the Polca community. Survey data show that the majority of respondents recommend joining the Polca community, citing reasons such as a positive atmosphere and support for Tay and New. Additionally, the survey also reveals that members of the Polca community take pride in their identity and find meaning in the community through reciprocal support and creativity. Interviews with Polca community members provide deeper insights into how they experience satisfaction and happiness in their participation. Emotional and social support among fellow fans, as well as creativity in expressing their love for Tay and New, are integral parts of their experience in this community. Participatory observation also highlights the importance of a sense of togetherness in strengthening social bonds among members of the Polca community. These members feel that their participation in the community is not just about being fans, but also about being part of a group that feels connected and accepted by each other. Thus, this research provides a deeper understanding of the Polca fandom phenomenon and significant contributions to the literature on popular culture, identity, and social media.